2013
DOI: 10.1016/j.cca.2013.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Novel genes detected by transcriptional profiling from whole-blood cells in patients with early onset of acute coronary syndrome

Abstract: Transcriptomic analysis by microarray technology demonstrated differential expression during a 48 h time course suggesting a potential use of some of these genes as biomarkers for very early stages of ACS, as well as for monitoring early cardiac ischemic recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 27 publications
5
40
1
Order By: Relevance
“…Statistically, these differences are suggestive and do not pass a strict Bonferroni correction for multiple testing. However, we do provide support for the increased expression of KCNE1 (p=0.00793) and ECHDC3 (p=0.0141) as well as decreased expression of MIAT (p=0.0449) in STEMI platelets compared to NSTEMI, as previously reported in whole blood, as well as increased expression of FKBP5 (p=0.000694) in platelets from STEMI patients (Table IIIb, Table IV) [21-23]. Our observation of increased MYL4 expression in NSTEMI compared to STEMI platelets is in the opposite direction as previously reported [21].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Statistically, these differences are suggestive and do not pass a strict Bonferroni correction for multiple testing. However, we do provide support for the increased expression of KCNE1 (p=0.00793) and ECHDC3 (p=0.0141) as well as decreased expression of MIAT (p=0.0449) in STEMI platelets compared to NSTEMI, as previously reported in whole blood, as well as increased expression of FKBP5 (p=0.000694) in platelets from STEMI patients (Table IIIb, Table IV) [21-23]. Our observation of increased MYL4 expression in NSTEMI compared to STEMI platelets is in the opposite direction as previously reported [21].…”
Section: Resultssupporting
confidence: 87%
“…However, we do provide support for the increased expression of KCNE1 (p=0.00793) and ECHDC3 (p=0.0141) as well as decreased expression of MIAT (p=0.0449) in STEMI platelets compared to NSTEMI, as previously reported in whole blood, as well as increased expression of FKBP5 (p=0.000694) in platelets from STEMI patients (Table IIIb, Table IV) [21-23]. Our observation of increased MYL4 expression in NSTEMI compared to STEMI platelets is in the opposite direction as previously reported [21]. Pathway analyses of suggestively differentially expressed genes (p≤0.05) showed enrichment for metabolic and mitochondrial-related pathways, including the synthesis of metabolic enzymes (panthothenate and CoA) and metabolism of nucleotide sugars, amino acids, and glycerophospholipids (Supplemental Tables 14-17).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…In a microarray-based gene expression study performed previously by our research team, we found that ECHDC3 mRNA expression was significantly increased within 2 h after an acute coronary syndrome, suggesting this gene could be a potential novel biomarker for the early stage of an acute episode [3]. However, the function of ECHDC3 or its involvement with cardiovascular diseases is scarcely explored in the literature, which might be due to its recent identification.…”
Section: Introductionmentioning
confidence: 99%